Beneficial Bacteria Associated With Silica Nanoparticles for Growth Promotion of Paspalum notatum - Amanda Carolina Prado de Moraes; Kathryn Louise Kingsley; Lucas da Silva Ribeiro; Bianca Baccili Zanotto Vigna; Emerson Rodrigues de Camargo; James Francis White; Alessandra Pereira Fávero; Paulo Teixeira Lacava (Applied and Environmental Soil Science)
Plant growth–promoting bacteria (PGPB) can play an essential role as biofertilizers to increase pasture efficiency and reduce the application of agrochemicals. Plant growth can be potentialized when these bacteria are combined with silica nanoparticles (SiNPs). The present study aimed to evaluate the effect of PGPB associated with SiNPs on the growth of bahiagrass (Paspalum notatum) seedlings. The PGPB were isolated from rhizospheric soils and leaves of Paspalum spp. grown in the tropical high-altitude region of Brazil and selected by their ability to fix nitrogen, solubilize phosphate, and synthesize indoleacetic acid (IAA). They were identified as Alcaligenes faecalis, Enterobacter asburiae, and Serratia marcescens by 16S rDNA sequencing. Spherical SiNPs (85 nm in diameter) were synthesized by the hydrolysis of the silicon precursor tetraethyl orthosilicate (TEOS), characterized by infrared spectroscopy and scanning electron microscopy (SEM) and applied at 5% (0.05 mg·mL−1) and 10% (0.1 mg·mL−1) concentrations. Disinfected P. notatum seeds were treated with PGPB, SiNPs, and PGPB + SiNPs and cultivated in magenta boxes containing peat, sand, and perlite. The seedlings were evaluated for their germination percentage, root length, shoot length, root dry weight, and shoot dry weight. Disinfected seeds subjected to the same treatments were also grown in Petri dishes containing 0.7% agarose. The roots of the seedlings in Petri dishes were stained with diaminobenzidine tetrahydrochloride (DAB) and visualized using a light microscope to confirm bacterial colonization. The three strains without SiNPs promoted the growth of P. notatum seedlings. S. marcescens treatment presented the greatest shoot length, and both concentrations of nanosilica with PGPB improved or maintained root lengths. Treatments of S. marcescens and E. asburiae with 10% SiNPs showed 100% seed germination. Seedlings inoculated with 10% SiNPs with S. marcescens and E. asburiae alone showed the highest shoot dry weight, and all treatments increased root dry weight compared to the control. The 10% SiNPs’ concentration inoculated with S. marcescens and A. faecalis positively affected P. notatum seedlings’ growth. This study suggests that nanosilica can be applied with PGPB to improve the development of bahiagrass and reduce the need for applications of agrochemicals.